Cu(II) and Pd(II) complexes of N-(2-hydroxybenzyl)aminopyridines - YALÇIN, BAHATTİN (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
N-(2-Hydroxybenzyl)aminopyridines (L) react with Cu(II) and Pd(II) ions to form complexes in the compositions Cu(Li)2(CH3COO)(2) center dot nH(2)O (n = 0.14), Pd(L-i)(2)Cl-2 center dot nC(2)H(5)OH (n = 0, 2) and Pd(L-2)(2)Cl-2 center dot 2H(2)O- In the complexes, the ligands are neutral and monodentate which coordinate through pyridinic nitrogen. Crystal data of the complexes obtained from 2-amino pyridine derivative have pointed such a coordinating route and comparison of the spectral data suggests the validity of similar complexation modes of other analog ligands. Cu(II) complex of N-(2-hydroxybenzyl)-2-aminopyridine (L), [Cu(L-1)(2)(CH3COO)(2)] has slightly distorted square planar cis-mononuclear structure which is built by two oxygen atoms of two monodentate carboxylic groups disposed in cis-position and two nitroaen atoms of two pyridine rings. The remaining two oxygen atoms of two carboxylic groups form two Cu and H bridges containing cycles which joint at same four coordinated copper(II) ion. IR and electronic spectral data and the magnetic moments as well as the thermogravimetric analyses also specify on mononuclear octahedric structure of complexes [Cu(L-2)(2)(CH3COO)(2) center dot 2H(2)O] and [Cu(L-3)(2)(CH3COO)(2) center dot 4H(2)O] where L-2 and L-3 are N-(2-hydroxybenzyl)-2- or 3-aminopyridines, respectively. X-ray analysis for [Pd(L-1)(2)Cl-2 center dot 2C(2)H(5)OH] show square planar environment around Pd(II) ion formed by two chlorine atoms in trans position and two nitrogen atoms of pyridine rings. The spectral data indicate structural similarity in the complexes obtained via ligand exchange between PdCl2(PhCN)(2) and 3-amino and 4-aminopyridine derivatives. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: aminopyridines; mononuclear copper complexes; mononuclear palladium complexes; Cu; H cycle; SCHIFF-BASE COMPLEXES; CRYSTAL-STRUCTURES; 2-AMINOPYRIDINE; LIGANDS; COPPER(II); SALTS